Network coding for hybrid satellite-terrestrial networks over non-identical fading channels - Jadoon, Muhammad Awais; Ali Khan, Zainab; Khan, Imran; Shah, Ahmad; Khalifa, Othman Omran (2013)
Satellite communication technology can well address for global communication system concern along imperative features. Network coding techniques are implicit for future wireless communication network demands in terms of throughput, security and robustness. Physical layer network coding (PNC) and Analog network Coding (ANC), are considered as two of the most studied variants of the network coding. Analysis revealed that similar performance augmentation can be made in satellite terrestrial networks with highly unpredictable behavior. In this paper feasibility study focuses on a comparative analysis amongst PNC and ANC in terrestrial land mobile satellite (LMS) networks in standings of their respective SER and outage probabilities.